1999
DOI: 10.1097/00007890-199911270-00026
|View full text |Cite
|
Sign up to set email alerts
|

Selective Deletion of Antigen-Specific, Activated T Cells by a Humanized Mab to Cd2 (Medi-507) Is Mediated by Nk Cells

Abstract: CD2 is a 50-kDa transmembrane glycoprotein that plays an important role in T and natural killer (NT) lymphocyte functions. CD2 serves as both an adhesion molecule and as a costimulatory molecule through interactions with its ligand, CD58, on antigen presenting or target cells. Consistent with earlier studies using a rat anti-CD2 mAb, we have shown that treatment of alloantigen stimulated T lymphocytes with a humanized mAb, MEDI-507 (IgG1, kappa), induced hyporesponsiveness to subsequent stimulation with alloan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
35
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 18 publications
1
35
0
2
Order By: Relevance
“…4C) strongly, suggesting that Fc + R engagement was essential for cytotoxicity. Previous results using the humanized version of BTI-322 (MEDI-507) have shown that deletion of activated T cells is also dependent on the Fc portion in this context, since F(ab') 2 fragments were unable to inhibit MLR and did not cause deletion of T or NK cells [21]. In fact, work using either MEDI-507 or BTI-322 have shown that removal of the NK cell population abolished the cytotoxic effects of CD2 stimulation [21,39], comparable with our results using alefacept.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…4C) strongly, suggesting that Fc + R engagement was essential for cytotoxicity. Previous results using the humanized version of BTI-322 (MEDI-507) have shown that deletion of activated T cells is also dependent on the Fc portion in this context, since F(ab') 2 fragments were unable to inhibit MLR and did not cause deletion of T or NK cells [21]. In fact, work using either MEDI-507 or BTI-322 have shown that removal of the NK cell population abolished the cytotoxic effects of CD2 stimulation [21,39], comparable with our results using alefacept.…”
Section: Discussionmentioning
confidence: 98%
“…Although monocytes have also been shown to exert antibody-dependent cell-mediated cytotoxicity (ADCC) [38], the cell lysis we observed was not attributed to monocyte populations since both T and NK cell cultures were subjected to plastic adherence and depleted of cells expressing CD14 and CD33. Previous studies have shown that CD2 mAb are also capable of triggering ADCC by activating NK cells resulting in CD2 + cell depletion [21,39]. In contrast, one study using the rat BTI-322 CD2 mAb reported T cell apoptosis by an NK cellindependent mechanism using F(ab') 2 fragments to mediate cell death [19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited expression of CD2 that is restricted to mature T cells and T-leukemic cells including MET-1 leukemic cells provides the scientific rationale for its use in antibody-mediated immunotherapy of ATL. MEDI-507 is a humanized mAb directed against CD2 that was genetically engineered from the rat version of the mAb (BTI-322) by BioTransplant (Charlestown, MA) for use in the prevention of allograft rejection [15][16][17] and in the therapy of graftversus-host disease (GVHD) and autoimmune diseases. 18 MEDI-507 (siplizumab) has been used in a series of phase 1 trials involving patients with psoriasis or with GVHD.…”
Section: Introductionmentioning
confidence: 99%
“…BTI-322, a rat IgG 2b κ anti-CD2 antibody suppressed renal allograft rejection as well as induced remissions in steroid-refractory graft-versus-host Hakimi et al (1993) disease (GvHD) in patients undergoing allogeneic bone marrow or stem cell transplant (Przepiorka et al, 1998). Siplizumab (MEDI-507; MedImmune, Inc.) is a humanized BTI-322 monoclonal antibody that has been studied for the treatment of severe psoriasis and for prophylaxis of GvHD because of its T-cell depleting properties (Branco et al, 1999;Koenecke et al, 2003;Shaffer et al, 2007). Zhang and co-wokers examined the anti- tumor activity of siplizumab and found it resulted in long-term disease-free survival of mice that had been inoculated with MET-1 human ATL cells (Zhang et al, 2003).…”
Section: Cd2mentioning
confidence: 99%